The Vertigos of Coining: 'Michel Houellebecq', Or, What Names Remain(s)?. Issue 2 (July 2021) - Dutton, James
Abstract : Writing remains. One could argue that it is precisely because of this uncanny and unpredictable survival that inscription holds an inextricable influence on culture. Deconstructive theory posits this as the 'biodegradability' of writing — that culture consumes writing's intended meaning, employing it as fuel for its own survival. In this article, I argue for Michel Houellebecq's awareness of this survival, suggesting that his texts stage their — and their author's — own biodegradability to interweave truth and fiction. Particularly, he utilizes the 'untranslatability' of the proper name — its brief resistance to cultural biodegradability — to intercept and write into the future(s) inscription is tied to. This draws attention to the vital paradox of proper names, and suggests that their untranslatability forces every reader to conjure different, contradicting and often 'out-of-sync' histories. Houellebecq's names, which necessitate an interminable coining, gesture to the inevitable (re)translation of finitude.